Assessing The Nutritional Status Of Orphaned And Non- Orphaned Children Aged 6-59 Months In Kakamega County, Kenya. (International Journal of Scientific Research and Management (IJSRM), 2018)
Child malnutrition is globally the highest risk factor for illness and death. It contributes to more than half of deaths in children worldwide. Children who lose their parents may face many hardships including food insecurity and poor child care resulting into malnutrition. However, in Kenya and the entire sub-Saharan Africa the problem of orphan-hood is expected to increase in the coming years due to more deaths from HIV/AIDS and other disasters. The objective of this study was to assess the nutritional status of orphaned and non-orphaned children. The study was a cross sectional study where both qualitative and quantitative methods were used. A structured questionnaire was administered to 306 care takers of orphans and non-orphans. The nutritional status of the children was determined by use of anthropometric measurements; weight for age (underweight), height for age (stunting) and weight for height (wasting) and pitting edema. Focus Group Discussions and key informant interviews were also conducted. Statistical package for Social Sciences (SPSS) and Emergency Nutrition Assessment (ENA) were used to analyze the data. Pearson chi-square and t-test statistics were used to test the significance of the relations while ranking was used to compare proportions of occurrence. The prevalence of malnutrition was high in the County (stunting 28.5%, wasting 6.9% and underweight 9.5% with wasting being more pronounced in Kakamega North Sub County. Boys were found to be more vulnerable to underweight (p value =0.025) and children aged 30-41 months were more stunted (p=0.009). However study found that there was no association between child malnutrition and orphan hood and therefore the children had equal chances of becoming malnourished it is recommended that the county and national governments should formulate and implement policies targeting all the children regardless of their orphan hood status. The County Integrated Plans (CIDPs) and national government policies need to stipulate well the nutrition intervention plans for the county.